KINERJA GURU PENDIDIKAN AGAMA ISLAM SELAMA PANDEMI COVID-19: Studi Verifikatif di Sekolah Dasar Negeri Padang Utara - Yusni Pasaribu; Riki Saputra; Ahmad Lahmi (Al-Muaddib : Jurnal Ilmu-Ilmu Sosial & Keislaman, 2021)
The performance of every professional person will not be different under any circumstances, even if the conditions are difficult. The covid-19 pandemic period is seen as a difficult time for all parties without the exception of Islamic religious education teachers. This article aims to reveal how the performance of Islamic religious education teachers in the covid-19 period, the information presented in this article in the form of verification of data found in the field. The approach used is in the form of a qualitative approach with a type of verification. Data is collected through observations, interviews and documentation studies. Data analysis techniques are interactive. The results of the study were the performance of Islamic religious education teachers in Padang Utara sub-district, first islamic religious education teachers had the same performance in academic aspects evidenced by the achievement of the completion of at least 100% of learners who passed 100% in religious subjects in Padang Utara Sub-district. These results can be verified with various documents and interview data on all parties who have ties to State Elementary School in Padang Utara Sub-District. Second, Islamic religious education teachers have a good performance in the administrator aspect, such as the ownership of syllabus, RPP, education calendar and learning media used during PAI learning in the Covid-19 period.